56 Peak Skin Dose evaluation for vascular clinical procedures in interventional radiology: a comparison between three computation numerical solutions. (December 2018) - Gardavaud, F.; Tavolaro, S.; Gussenmeyer-Mary, N.; Cornelis, F.; Boudghène, F.
Abstract : Introduction: This study compared the Peak Skin Dose (PSD) evaluation performed by a dose monitoring software with two other numerical solutions for interventional clinical procedures realized in an angiographic room. Methods: 26 Patients, with standard Body Mass Index, have benefited interventional vascular procedures, performed in an angiographic room (GE Innova IGS 540, GE HealthCare, Buc, France). For each clinical case, evaluated on various embolization conditions, PSD calculations were performed across three numerical solutions: with Em.Dose v 3.0.1[1] (Esprimed, Villejuif, France), noted PSD EmDose ; with Innova DoseMap[2] (GE HealthCare, Buc, France), noted PSD Innova and with DoseWatch v2.3 (GE HealthCare, Buc, France), noted PSD DoseWatch . 3D-angiographic acquisitions were taken into account for all the PSD calculation solutions. Log files were retrieved to get PSD Innova . The use of the super elliptical phantom computation model, tailored for each patient, was always forced to get the most accurate PSD EmDose values estimated from DICOM files including all the angiographic sequences (2D and/or 3D) and all the fluoroscopy sequences registered by the operator. For the three numerical solutions, a calibration factor, to take into account DAP-meter flat chamber measuring error, was integrated to calculate all the PSD values. PSD DoseWatch values were statistically compared with PSD Innova values and PSD EmDose values. Results: PSD mean values were 560 ± 540 mGy, 559 ± 494 mGy and 571 ± 551 mGy for PSD DoseWatch, PSD Innova and PSD EmDose respectively. PSD DoseWatch values was strongly correlated to the PSD Innova values and also to the PSD EmDose values (P > 0.9999 for each combination with Dunn multiple comparisons non-parametric test). Conclusions: Based on this study, PSD DoseWatch values are consistent to be used in clinical routine by experienced and trained medical physicists when patients benefit interventional vascular procedures, involving thoracic, abdominal and/or pelvic exposure area, in an angiographic room with a single X-rays tube.